The Role of family mediation in conflict resolution: international experience and prospects for Kazakhstan - Abugaliyeva, F.; Zhaskairat, M. (Bulletin of the Karaganda University “Law Series”, 2025)
The article explores the role of family mediation in conflict resolution, analyzes international experience in its application, and examines prospects for its development in Kazakhstan. Particular emphasis is paid to the advantages of mediation compared to litigation, and based on the analysis of foreign practices, key mechanisms and models of family mediation that can be adapted in Kazakhstan are highlighted. In the course of the research, the following methods of the scientific research were used: specifically sociological, comparative legal, formal legal, statistical, logical, system-structural, functional. Based on the methods of scientific research, the concept and essence of family mediation were comprehensively revealed. In addition, family mediation is applicable for conflict resolution in the conduct of family business. In conclusion, recommendations are proposed for improving the national legal framework and developing the institution of family mediation in the country, as well as the possibility of applying family mediation in resolving disputes related to family entrepreneurship.